Festival Lima Gunung : Strategi Identitas Lokal Masyarakat Di Lereng Gunung Di Jawa Tengah - Fitriasari, Paramitha Dyah (Universitas Negeri Makassar, 2017)
Five Mountains Festival is the party of the people who regularly held one year, is a representation of local culture. Prepare all kinds of both performance and visual arts which were the work of the villagers around. The potential is there in five mountain communities are quite large and intertwined emotional bond between the artists and the public. Artists vying to display the distinctive traditions of each village by displaying characteristic and new creativity in the grand event.